Cryptic Female Choice in Arthropods 2015
DOI: 10.1007/978-3-319-17894-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Post-copulatory Sexual Selection in Two Tropical Orb-weaving Leucauge Spiders

Abstract: This chapter focuses on descriptive and experimental studies of the sexual biology of two spider species, Leucauge mariana and Leucauge argyra. We examine general questions related to female effects on paternity by taking advantage of several unusual traits: direct female participation in forming copulatory plugs and physical clasping by the female rather than the male during copulation in both species; and derived traits in the genitalia of males and females and occasional female cannibalism of conspecific ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
2
13
1
Order By: Relevance
“…However, male deposition of chemicals that form mating plugs is not the only trait that influences sperm competition. Females can also determine the efficacy of plug formation through the production or deposition of additional secretions (Aisenberg, Barrantes, & Eberhard, ; Uhl et al., ). In some spiders, the deposition of substances by females prior to mating plug formation alters the efficacy of plugs, but the propensity to do so depends on the quality of the males’ performance during courtship or mating (Aisenberg & Barrantes, ; Aisenberg & Eberhard, ; Kuntner, Gregorič, Zhang, Kralj‐Fišer, & Li, ; Uhl et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, male deposition of chemicals that form mating plugs is not the only trait that influences sperm competition. Females can also determine the efficacy of plug formation through the production or deposition of additional secretions (Aisenberg, Barrantes, & Eberhard, ; Uhl et al., ). In some spiders, the deposition of substances by females prior to mating plug formation alters the efficacy of plugs, but the propensity to do so depends on the quality of the males’ performance during courtship or mating (Aisenberg & Barrantes, ; Aisenberg & Eberhard, ; Kuntner, Gregorič, Zhang, Kralj‐Fišer, & Li, ; Uhl et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…(Aisenberg et al. ) and Physocyclus globosus (Peretti et al. ), male genital behavior is correlated with sperm usage patterns, suggesting species‐specific stimulation of the female, but support is less convincing because several of the additional tests in Table are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although very little is known, similar cryptic female mechanisms have been described in spider species. In the genus, Physocyclus females would eject males' sperm depending on their copulatory courtship performance (Peretti & Eberhard, ), or among the spider genera Lactrodectus , Leucage and Argiope it seems possible that females can bias fertilisation of their eggs by controlling the mating plug formation (Aisenberg, Barrantes, & Eberhard, ; Andrade & MacLeod, ; Schneider, Uhl, & Herberstein, ). Beyond the mechanisms, it has been also suggested that female spiders can selectively store sperm of courting males (Schneider & Lesmono, ), cannibalised males (Herberstein et al., ) and gift‐giving males (Albo, Bilde, & Uhl, ).…”
Section: Discussionmentioning
confidence: 99%